Prognostic significance of suboptimal secondary prevention pharmacotherapy after acute coronary syndromes. Issue 3 (18th March 2021) - Yudi, Matias B.; Farouque, Omar; Andrianopoulos, Nick; Ajani, Andrew E.; Brennan, Angela; Murphy, Alexandra C.; Lefkovits, Jeffrey; Reid, Christopher M.; Oqueli, Ernesto; Sebastian, Martin; Duffy, Stephen J.; Clark, David J.; et al.
Abstract: Background: Optimal secondary prevention pharmacotherapy is the cornerstone of post‐acute coronary syndrome (ACS) management. The prognostic impact of not receiving five guideline‐recommended therapies is poorly described. Aim: To ascertain the prognostic significance of suboptimal pharmacotherapy in ACS survivors. Methods: Consecutive patients with ACS from the Melbourne Interventional Group registry who were alive at 30 days following their index percutaneous coronary intervention were included. Patients were divided into three categories based on the number of secondary prevention medications prescribed. The optimal medical therapy (OMT), near‐optimal medical therapy (NMT), suboptimal medical therapy (SMT) groups were prescribed 5, 4 and ≤ 3 medications, respectively. Primary endpoint was long‐term mortality. Cox‐proportional hazard modelling was undertaken to assess independent predictors of survival. Results: Of the 9375 patients included, 5678 (60.6%) received OMT, 2903 (31.0%) received NMT and 794 (8.5%) received SMT. Patients receiving SMT were older, more likely to be female and had higher burden of comorbidities (renal impairment, congestive heart failure, diabetes, peripheral vascular disease; P < 0.01 for all). SMT was associated with higher long‐term mortality at 3.9 ± 2.2 years when compared to NMT and OMT (16.8% vs 10.5% vs 8.2%, P < 0.001). Compared to OMT, SMT was an independent predictor of long‐term mortality (hazard ratio, HR 1.62, 95% confidence interval, CI 1.30–2.02, P < 0.01) while NMT was associated with a clinically significant 14% mortality hazard (HR 1.14, 95% CI 0.97–1.34, P = 0.11). Conclusions: There is a graded long‐term hazard associated with not receiving OMT after an ACS. Improvements in secondary prevention pharmacotherapy models of care are warranted to further decrease the long‐term mortality.